2007
DOI: 10.2967/jnumed.106.039354
|View full text |Cite
|
Sign up to set email alerts
|

99mTc-HMPAO SPECT Study of Cerebral Perfusion After Treatment with Medication and Electroconvulsive Therapy in Major Depression

Abstract: Compromised regional cerebral blood flow (rCBF) in major depressive disorder may be partly reversed by successful antidepressant treatment. However, it is not known if the reversal of rCBF compromise is dependant on the mode of antidepressant treatment. The current study aimed to address this question. Methods: Thirty-three patients (19 women and 14 men; mean age 6 SD, 53 6 16 y) with moderate major depressive disorder were studied before 6 wk of treatment with tricyclic antidepressants, selective serotonin re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 25 publications
4
39
1
1
Order By: Relevance
“…[19] Hypofrontality was shown to be associated with severe negative symptoms rCBF in depressed patients before treatment was lower than in healthy controls, and a response to medication was associated with an increase in cerebral perfusion. [20] Though there has been perfusion change between pre-treatment and post treatment groups, but in our study we were unable to find significant difference between these two groups ECD is a sensitive agent for detecting abnormalities characterized by neuronal necrosis, the present study suggests that it is less sensitive as a tracer for identifying the more subtle abnormalities of functional psychiatric disorders when compared with PET scan…”
Section: Visual Inspection Of the Imagescontrasting
confidence: 50%
“…[19] Hypofrontality was shown to be associated with severe negative symptoms rCBF in depressed patients before treatment was lower than in healthy controls, and a response to medication was associated with an increase in cerebral perfusion. [20] Though there has been perfusion change between pre-treatment and post treatment groups, but in our study we were unable to find significant difference between these two groups ECD is a sensitive agent for detecting abnormalities characterized by neuronal necrosis, the present study suggests that it is less sensitive as a tracer for identifying the more subtle abnormalities of functional psychiatric disorders when compared with PET scan…”
Section: Visual Inspection Of the Imagescontrasting
confidence: 50%
“…If the ar ticles were written in other languages, they were translated into English for assessment. In all, 5 SPECT studies, 8,9,[33][34][35] 8 PET studies, 6,7,36-41 1 ASL study 10 and 9 regional homogeneity studies [11][12][13]17,[42][43][44][45][46] met our inclusion criteria (Table 1). All these papers were written in English.…”
Section: Meta-regression Analysismentioning
confidence: 99%
“…This findings is presumed to be related to clinical responsiveness (Prohovnik et al, 1986;Rosenberg et al, 1988;Guze et al, 1991). However, some studies have demonstrated significant increases in rCBF in several brains (Bonne et al, 1996;Kohn et al, 2007). These discrepancies might be due to several confounding factors, such as procedural-related factors including anesthetics and electrode replacements, or to varying durations between the termination of the ECT course and imaging scanning.…”
Section: Change Of Rcbf/rgmr Induced By Antidepressants and Ectmentioning
confidence: 99%